Dynamic eye avoidance patterns in the high autistic traits group: An eye-tracking study - Xue, Huiqin; Zhang, Ludan; Wang, Junling; Liu, Wei; Liu, Shuang; Ming, Dong (Frontiers in Psychiatry, 2023)
Reduced fixation to the eye area is the main characteristic of social deficits associated with Autism Spectrum Disorder, a similar pattern may exist in individuals with high autistic traits. However, their scanning patterns to the eye area of emotional faces are still unclear on the time scale. In the present study, we recruited 46 participants and divided them into the high autistic traits (HAT) group (23 participants) and the low autistic traits (LAT) group (20 participants) based on their Autism-Spectrum Quotient (AQ) scores. Moreover, we captured their eye movement patterns when observing different angular emotional faces. We extracted the proportional fixation time to the eye area under different time windows. The results showed that the fixation time of the HAT group was always significantly smaller than that of the LAT group (p < 0.05), and the difference between the two groups increased in the middle and late stages of face presentation. The results of the linear regression analysis showed that the proportional fixation time was negatively correlated with AQ scores (p < 0.05), indicating that the proportional fixation time to the eye area could be a potential indicator to measure the level of autistic traits. We then calculated the latency to orient the eye area and the latency to disengage the eye area to explore the priority of observation of the eyes. The results showed that compared with the LAT group, the HAT group has a longer latency to orient the eye area (p < 0.05) and has longer latency to disengage the eye area (p < 0.05), illustrating that the HAT group saw the eyes more slowly and left them faster.